Robot gesture and user acceptance of information in human-robot interaction - Kim, Aelee; Kum, Hyejin; Roh, Ounjeong; You, Sangseok; Lee, Sukhan (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
This study explores how human users respond to coordinated and uncoordinated gestures of a robot as an information deliverer. A between-subject experiment was conducted using the Wizard of Oz method, with 63 participants randomly assigned to one of four conditions (voice-only vs. no-gesture vs. coordinated gesture vs. uncoordinated gesture) taking an artwork class in a museum-like setting. The robot was explaining the information of the artworks with modalities accordingly designed to each condition. Results showed that the coordinated gesture was not aiding information delivery. However, there were notable relations between the coordinated gesture and intimacy, homogeneity, and involvement. These results have theoretical implications for cognitive load of working memory and practical implications for designing and deploying dynamic humanoid robots for museum tour guide.